Kylmä kyyti traktorilla - Koskenmäki, Voitto; Tasanen, Tapani (Metsäntutkimuslaitos, 2011)
Kirja: Vilkuna, T. 2010. Kylmä kyyti traktorilla. Metsäkustannus, Helsinki. 123 s. ISBN 978-952-5694-49-9.
Kirja-arvostelu